2021
DOI: 10.3390/microorganisms9030548
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Follow-Up of Patients Treated with Fecal Microbiota Transplantation for Recurrent Clostridioides difficile Infection from a Randomized Controlled Trial and Review of the Literature

Abstract: Fecal microbiota transplantation (FMT) has become a well-established treatment for recurrent Clostridioides difficile infection (rCDI). While short-term outcomes and adverse events relating to FMT have been well documented, there still is a paucity of data with regard to long-term safety. In this report, we describe the long-term follow-up of the prospective cohort of the first randomized controlled trial of FMT for rCDI, and review the existing literature. A total of 34 patients were treated with FMT for rCDI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…60 One study 64 reported that there was a slightly higher incidence of myocardial infarction in FMT group compared with non-FMT at 1 year follow-up, but that the incidence of other conditions was similar. At 10-year follow-up, one study 65 reported that there were no new diagnoses of autoimmune diseases, gastrointestinal disorders or malignancies and that there were no deaths which were attributed to FMT.…”
Section: New or Worsening Symptoms Following Fmtmentioning
confidence: 99%
“…60 One study 64 reported that there was a slightly higher incidence of myocardial infarction in FMT group compared with non-FMT at 1 year follow-up, but that the incidence of other conditions was similar. At 10-year follow-up, one study 65 reported that there were no new diagnoses of autoimmune diseases, gastrointestinal disorders or malignancies and that there were no deaths which were attributed to FMT.…”
Section: New or Worsening Symptoms Following Fmtmentioning
confidence: 99%
“…29 However, reassuringly, no significant delayed complications or adverse effects related to infections have been described in longitudinal studies looking at long term follow up of patients who have received FMT administration. 30–32 …”
Section: Fecal (Or Intestinal) Microbiota Transplantation (Fmt/imt)mentioning
confidence: 99%
“…This method reduces intestinal inflammation, as demonstrated by decreased levels of proinflammatory cytokines such as TNF-a, IL-1b, and interferon-g (IFN-g), and helps in restoring the intestinal homeostasis. It has been successfully used for treating recurrent and antibiotic-refractory C. difficile infections (107)(108)(109)(110), even in pediatric patients (111).…”
Section: Modulation Of Microbiota Compositionmentioning
confidence: 99%